Corneal Transplant Infection due to Alternaria alternata: A Case Report - Vasileios Konidaris; Andreana Mersinoglou; Timoleon-Achilleas Vyzantiadis; Domniki Papadopoulou; Kostas G. Boboridis; Panagiotis Ekonomidis (Case Reports in Ophthalmological Medicine, 2013)
Purpose. To report a case of Alternaria alternata keratitis in a patient with a corneal transplant in her right eye due to bullous pseudophakic keratopathy. Methods. A 66-year-old female underwent a full-thickness keratoplasty in her right eye due to bullous pseudophakic keratopathy. Three weeks after keratoplasty, epithelial edema and a stromal opacity with an infiltrate and development of peripheral corneal opacities appeared. The diagnosis of Alternaria alternata keratitis was made. Results. The patient underwent a second keratoplasty, due to the corneal melting as a result of the fungal infection. She was also given combined antifungal treatment locally and systematically. Conclusion. Corneal transplantation alone would not have been sufficient to keep the fungus in the anterior portion of the eye. Combined antifungal treatment, locally and systematically, was important in attempting to prevent the further spread of the fungus to the interior of the eye. To our knowledge, the case presented here is only the second one in the literature concerning a keratomycosis due to Alternaria alternata corneal transplant infection.